CHARACTERISTIC OF SUDDENT INFANT DEATH SYNDROME (SIDS) KNOWLEDGE OF GENERAL PRACTITIONER IN BANDUNG CITY AT 2020 - Andri Andrian R; Elly Noer Rochmah; Dafha Braza Musti (Jurnal EduHealth, 2022)
Sudden Infant Death Syndrome (SIDS) is the death of an infant without known cause after comprehensive examination including scene investigation, autopsy, and history of the previous disease. Knowledge is the result of know something after sense a certain object. The incidence of SIDS in 2007 was 2.5% of the total neonatal mortality rate in Indonesia. This study's purpose is to understand the level of SIDS knowledge of general practitioners and risk factors for SIDS known by general practitioners. This is a descriptive survey study with a total of 58 general practitioners who provide health services as respondents. The sample is chosen by purposive sampling technique. The majority of respondents are women with an average age range from 26-35 years old. Sixty-nine percent respondent has a good level of SIDS knowledge and sixty-seven point two respondent notes preterm born as a possible risk factor for SIDS. This level of knowledge on SIDS may be caused by low detected cases of SIDS in Indonesia. From this result, we suggest holding more symposiums about SIDS that aim to increase general practitioner ability to diagnose SIDS